Orangia highways (B) - Es?, P?ter, (SAGE Knowledge. Cases., 2006)
In part B of this case students focus on procurement auctions from the bidders' point of view and are asked to develop the optimal bidding strategy in a first-price auction for a risk-neutral bidder and calculate the value of knowing the number of one's opponents.